The Neuromarketing: Bridging Neuroscience and Marketing for Enhanced Consumer Engagement - Guo Song; Md. Abu Issa Gazi; Abdul Waaje; Md. Mustaqim Roshid; Rejaul Karim; Md. Atikur Rahaman; Zhang Min; Abdul Rahman Bin S. Senathirajah (IEEE Access, 2025)
This review paper examines the influence of neuromarketing on consumer behavior research, emphasizing its origins, methodologies, impacts, and implications for customer engagement. This paper conducts a thorough narrative literature review on neuromarketing, analyzing the application of diverse neuroscientific techniques, including functional magnetic resonance imaging (fMRI), electroencephalography (EEG), positron emission tomography (PET), magnetoencephalography (MEG), and facial coding/eye tracking, to assess cerebral responses and forecast consumer behavior. Recent scholarly investigations underscore how neuromarketing utilizes contemporary breakthroughs to transform consumer behavior research by offering enhanced insights into cognition and emotion. These sophisticated tools have contested conventional study methodologies, facilitating a more comprehensive comprehension of the interaction between marketing stimuli and the brain. The theoretical and practical aspects of the findings are that advanced neuroimaging techniques like fMRI, EEG, and eye-tracking have revealed the complex interactions between emotions, attention, and memory that traditional methods and neuromarketing transform marketing by giving marketers new tools and approaches to boost results. This review synthesizes previous research on the topic, highlighting the necessity for equilibrium between scientific advancement and ethical accountability in neuromarketing, thereby benefiting both academic and commercial sectors.